Investment timing, agency, and information - Grenadier, Steven R.; Wang, Neng (Journal of Financial Economics, 2005)
This paper provides a model of investment timing by managers in a decentralized firm in the presence of agency conflicts and information asymmetries. When investment decisions are delegated to managers, contracts must be designed to provide incentives for managers to both extend effort and truthfully reveal private information. Using a real options approach, we show that an underlying option to invest can be decomposed into two components: a manager's option and an owner's option. The implied investment behavior differs significantly from that of the first-best no-agency solution. In particular, greater inertia occurs in investment, as the model predicts that the manager will have a more valuable option to wait than the owner.